Analisa Penanggulangan Banjir Kali Lamong Kabupaten Gresik - Enggar Ika Winahyu; Minarni Nur Trilita; Novie Handajani (Jurnal Rekayasa Sipil dan Lingkungan, 2022)
The Lamong river is located in East Java Province, the Lamong river watershed covers a number of areas, namely Lamongan and Mojokerto Regencies. The upstream part of the Lamong River is in the Lamongan and Mojokerto Regencies, while the downstream part is located on the border of Surabaya and Gresik City, and empties into the Madura Strait. Lamong river has a length of ±103 km and a width of ±50 m with an area of +720km². During the rainy season, the Lamong river often floods. This flood is due to backwater and the channel cross-section is unable to accommodate the existing discharge. The purpose of this research is to find out the actions that will be taken to overcome the flood caused by the overflow of the Lamong river and need an alternative to overcoming the flood problem, one of which is raising the embankment. The steps to achieve these goals are hydrological analysis and hydraulics analysis. The hydrological analysis consists of calculating the average rainfall, calculating the planned rainfall, testing the suitability of the frequency distribution, calculating the flood discharge, and calculating the cross-sectional capacity of the river. Hydraulics analysis using the HEC-RAS program. The results of the analysis obtained that the Lamong river flood control used a 25-year return period, and planned flood control by adding the height of the embankment at the overflowing point of the river. Segment II Q = 167.68 m³/s with the addition of the right and left embankments as high as 2-5 meters. Segment III Q = 274.65 m³/s with the addition of the right and left embankments as high as 2-5 meters. Segment IV Q = 352.14 m/s with the addition of the right and left embankments as high as 2-3 meters. ABSTRAK Kali Lamong terletak di Provinsi Jawa timur, DAS Kali Lamong meliputi sejumlah daerah yaitu Kabupaten Lamongan dan Mojokerto. Bagian hulu Kali Lamong terletak di kabupaten Lamongan dan Mojokerto, sedangkan bagian hilir terletak di perbatasan Kota Surabaya dan Gresik, serta bermuara ke Selat Madura. Kali Lamong memiliki panjang Kali ±103 km dan lebar Kali ± 50 m dengan luas Daerah Aliran Kali (DAS) ±720km². Saat musim hujan Kali Lamong sering terjadi banjir. Banjir ini dikarenakan aliran balik (backwater) dan dimensi penampang saluran tidak mampu menampung debit yang ada. Tujuan dari penelitian ini adalah untuk mengetahui tindakan yang akan dilakukan untuk mengatasi banjir akibat luapan Kali Lamong , serta memerlukan alternatif dalam mengatasi permasalahan banjir yang tepat salah satunya meninggikan tanggul. Tahapan untuk mencapai tujuan tersebut dilakukan analisa hidrologi dan analisa hidrolika. Analisa hidrologi yang terdiri dari perhitungan curah hujan rata –rata, perhitungan curah hujan rencana, uji kesesuaian distribusi frekuensi, perhitungan debit banjir, perhitungan kapasitas penampang Kali. Analisa hidrolika menggunakan bantuan program HEC-RAS. Hasil analisa diperoleh pengendalian banjir Kali Lamong menggunakan kala ulang 25 tahun, dan direncanakan pengendalian banjir dengan penambahan tinggi tanggul pada titik Kali yang meluap. Segmen II Q = 167.68 m3/dt dengan penambahan tinggi tanggul kanan dan kiri setinggi 2-5 meter. Segmen III Q = 274.65 m3/dt dengan penambahan tinggi tanggul kanan dan kiri setinggi 2-5 meter. Segmen IV Q = 352.14 m/s dengan penambahan tinggi tanggul kanan dan kiri setinggi 2-3 meter.